Diversity of muskox Ovibos moschatus (Zimmerman, 1780) (Bovidae, Mammalia) in time and space based on cranial morphometry. (2nd January 2021) - Stefaniak, Krzysztof; Lipecki, Grzegorz; Nadachowski, Adam; Semba, Agata; Ratajczak, Urszula; Kotowski, Adam; Roblíčková, Martina; Wojtal, Piotr; Shpansky, Andrey V.; Malikov, Dmitriy G.; Krakhmalnaya, Tatiana V.; Kovalchuk, Oleksandr M.; et al.
ABSTRACT: Muskox Ovibos moschatus is a Pleistocene relic, which has survived only in North America and Greenland. During the Pleistocene, it was widely distributed in Eurasia and North America. To evaluate its morphological variability through time and space, we conducted an extensive morphometric study of 217 Praeovibos and Ovibos skull remains. The analyses showed that the skulls grew progressively wider from Praeovibos sp. to the Pleistocene O. moschatus, while from the Pleistocene to the recent O. moschatus, the facial regions of the skull turned narrower and shorter. We also noticed significant geographic differences between the various Pleistocene Ovibos crania. Siberian skulls were usually larger than those from Western and Central Europe. Eastern European muskoxen also exceeded in size those from the other regions of Europe. The large size of Late Pleistocene muskoxen from regions located in more continental climatic regimes was probably associated with the presence of more suitable food resources in steppe-tundra settings. Consistently, radiocarbon-dated records of this species are more numerous in colder periods, when the steppe-tundra was widely spread, and less abundant in warmer periods.